Rola skojarzeń w kreowaniu wizerunku jednostki terytorialnej: The role of associations in creating the image of a territorial unit - Chrząścik, Marcin (Management and Administration Journal, 2021)
The complex and long-term process of creating an image of such a specific subject as a territorial unit, primarily involves the development of its recognition. The fact that this recognition should be overwhelmingly positive - and rightly so - is the undisputed, obvious objective of all the activities of creating the image. There’s a reason why in most of theoretical concepts, an image of the city is defined in terms of a complex set of "mental creations", and it is underlined that the process of a city identification is based on associations. This article is about the positive and negative aspects of the associations connected with the city processes of communication.